A novel method for the probabilistic assessment of ship grounding damages and their impact on damage stability. (January 2023) - Taimuri, Ghalib; Ruponen, Pekka; Hirdaris, Spyros
Highlights: A novel method for probabilistic assessment of ship grounding is presented. External dynamics are modelled by a contact mechanics FSI model accounting for evasiveness in real operational conditions. Probabilistic estimates are evaluated by Monte Carlo simulations. Ship damage stability is carried out using NAPA software. Comparisons of the extents of damage derived from the new method against EU EMSA historical data records indicate larger estimates of ship's damage length. Abstract: Existing statistics for use in ship damage stability assessment are based on either accident investigation reports or empirical crew records. This is the reason why the databases used within the context of ship design for safety are either incomplete or miss critical information. This paper introduces a methodology for the probabilistic evaluation of passenger ship damage extents. The model accounts for the influence of crashworthiness in real operational conditions. Based on operational statistical records for ships before grounding, a Monte Carlo simulation is utilized to randomly generate a realistic profile that accounts for variable ship speed, conical rock geometry, rock position, and height in both deep and shallow waters. Subsequently, using the operational parameters as input, a six degrees of freedom fluid–structure interaction (FSI) model is used to combine the influence of ship dynamics, and structural mechanics on the probability distributions of hull breaches. Ship damage stability evaluation is carried out using NAPA software, which measures ship survivability via an attained subdivision index. Probabilistic results are compared against existing distributions of damage extents and demonstrate an increase in the mean distribution of damage length. The findings demonstrate the method's adequacy for improving passenger vessel safety in case of ship grounding. It is concluded that the method allows for low-fidelity optimization of the structural arrangement of the bottom of the ship, probabilistic evaluation of loads associated with ship crashworthiness, and the assessment of operational limitations during an evasive maneuver. It could therefore be used for the future development of ship damage stability standards or ad - hoc forensic investigations.